The influence of interior architecture in the health space intended for pediatric treatment - Oliveira, Josyê Fernanda Fritzen; Kleinschmitt, Elisiana Alves (Seven Editora, 2023)
This article aims to demonstrate the importance and influence of interior architecture in pediatric hospital treatment, considering that these spaces are usually cold and frightening, being even more impactful for children. Thus, the study seeks to identify the interference of the insertion of the concept of humanization in health spaces intended for children (children aged 0 to 12 years), which contributes to the reduction of traumatic episodes. In this sense, the discussion of humanization becomes essential, mainly due to the search to reduce the anxiety, restlessness and stress caused in the small patients and in all those involved in the process. The objective of this article is to establish a direct relationship between the humanization of space, through interior architecture, and the health environment, and to present strategies for the inclusion of the concept in pediatric institutions. To achieve the purpose, the research brings together case studies in the following hospitals: Nelson Mandela Children’s Hospital (Johannesburg, South Africa), EKH/IF Children’s Hospital - Integrated Field (Samut Sakhon, Thailand) and Nemours/Stanley Beaman & Sears Children’s Hospital (Orlando, United States), pointing out solutions that prove the insertion of strategic approaches that aim at a humanized space and care. Thus, this work highlights the effect of interior architecture on the psychological and treatment process of the little patient, which directly impacts companions and employees, who form a multidisciplinary team in care. The interior architecture, combined with the humanized health space, provides a welcoming, quiet, and pleasant environment, facilitating and speeding up the care of health professionals, as well as making the experience lighter and more fun for the infant. DOI:https://doi.org/10.56238/interdiinovationscrese-040